HUBUNGAN POSTUR JANGGAL DENGAN KEJADIAN LOW BACK PAIN PADA PEMANEN SAWIT DI KABUPATEN PELALAWAN - Yessi Rahayu; Retno Putri; Liqqa Muqita Supriadi (Collaborative Medical Journal, 2024)
LBP is the most common work-related musculoskeletal disorder. Lower back pain (LBP) is not a disease or diagnosis. At least 80% of people have experienced LBP. Personal, environmental, and work-related factors can all contribute to LBP. The primary cause of LBP is poor work posture. Palm oil harvesters frequently pose awkwardly. To be diagnosed with LBP, the subject must have had it for a year and have paralumbar or gluteal muscle tenderness, as well as radiating lower leg pain. This study investigates awkward posture and low back pain among palm oil harvesters. This study is cross-sectional. This 75-person study was carried out at Pelalawan Regency. The sampling method was simply random. The data was collected using a questionnaire. According to the Spearman test, an awkward posture is associated with low back pain (LBP) (p-value = 0.019)